مفهوم الذات لدى تلاميذ ذوي السمنة للممارسين للانشطة الرياضية - غالم, شمس الدين; بخدومة, عبد الوهاب (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
وتهدف الدراسة التي بين أيدينا إلى محاولة معرفة مفهوم الذات لدى التلاميذ ذوي السمنة الممارسين وغير الممارسين للأنشطة الرياضية، ولأجل ذلك اتبعنا المنهج الوصفي، حيث تكونت عينة الدراسة من ذوي السمنة الممارسين وغير الممارسين للأنشطة الرياضية بولاية مستغانم، واستعملنا مقياس مفهوم الذات كأداة للدراسة، واستخدمنا لتحويل البيانات الى نتائج إحصائية معامل (الصدق، الثبات، معامل الارتباط البسيط لبيرسون)، وجاءت أهم نتائج الدراسة وجود فروق ذات دلالة معنوية بين التلاميذ ذوي السمنة الممارسين وغير الممارسين للأنشطة الرياضية في بعد الذات الجسمية لصالح التلاميذ الممارسين للأنشطة الرياضية، وعدم وجود فروق ذات دلالة معنوية بين التلاميذ ذوي السمنة الممارسين وغير الممارسين للأنشطة الرياضية في بعد الذات الشخصية، اما اهم الاقتراحات والتوصيات فتمثلت بداية بضرورة الاهتمام بالأنشطة الرياضية التي تحسن من مفهوم الذات لدى ذوي السمنة، واقتراح برامج إدماجيه رياضية للتلاميذ الغير الممارسين للأنشطة الرياضية من ذوي السمنة. // // // // Self-concept among obese students who practice and do not practice sports activities The study at hand aims to try to know the self-concept of obese students who practice and do not practice sports activities. To do this, we followed the descriptive approach, as the study sample consisted of obese students who practiced and did not practice sports activities in the state of Mostaganem. We used the self-concept scale as a tool for the study, and we used it to transform The data are divided into statistical results, coefficients (honesty, reliability, and Pearson’s simple correlation coefficient). The most important results of the study were the presence of significant differences between obese students who practice and do not practice sports activities in the dimension of the physical self, in favor of students who practice sports activities, and the absence of significant differences. Among obese students who practice and do not practice sports activities in the personal self dimension. The most important suggestions and recommendations were initially the necessity of paying attention to sports activities that improve the self-concept of people with obesity, and proposing sports integration programs for obese students who do not practice sports activities. // // // //
LAPA-2024-12
Keywords: مفهوم الذات- السمنة-الأنشطة الرياضية // // : self-concept – obesity - sports activities